2010
DOI: 10.1073/pnas.1006677107
|View full text |Cite
|
Sign up to set email alerts
|

Nominally hydrous magmatism on the Moon

Abstract: For the past 40 years, the Moon has been described as nearly devoid of indigenous water; however, evidence for water both on the lunar surface and within the lunar interior have recently emerged, calling into question this long-standing lunar dogma. In the present study, hydroxyl (as well as fluoride and chloride) was analyzed by secondary ion mass spectrometry in apatite [Ca 5 ðPO 4 Þ 3 ðF,Cl,OHÞ] from three different lunar samples in order to obtain quantitative constraints on the abundance of water in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
189
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(196 citation statements)
references
References 65 publications
5
189
0
2
Order By: Relevance
“…Recent detections of dissolved water in lunar volcanic glasses and melt inclusions (Saal et al 2008;Hauri et al 2011;Saal et al 2013;Chen et al 2015;Wetzel et al 2015), lunar apatites (Boyce et al 2010;McCubbin et al 2010;Greenwood et al 2011;Tartèse et al 2014), and plagioclase from lunar highland anorthosites (Hui et al 2013) have led to a reevaluation of what has appeared for decades to be one of the definitive results of the study of lunar samples: i.e., that the sources of lunar magmas-and, by inference, the entire Moon-are much poorer in water than the Earth; indeed the Moon had been described as "bone dry" (Newsom and Taylor 1989). In particular, direct measurements of water in incompletely degassed, primitive lunar glasses made in several laboratories have shown that water concentrations are similar to those observed in magmas from Earth's depleted upper mantle (Saal et al 2008;Chen et al 2015;Hauri et al 2015;Wetzel et al 2015) and that the isotopic composition of this water is approximately chondritic (Friedman et al 1974;Saal et al 2013;Barnes et al 2014;Füri et al 2014;Tartèse et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent detections of dissolved water in lunar volcanic glasses and melt inclusions (Saal et al 2008;Hauri et al 2011;Saal et al 2013;Chen et al 2015;Wetzel et al 2015), lunar apatites (Boyce et al 2010;McCubbin et al 2010;Greenwood et al 2011;Tartèse et al 2014), and plagioclase from lunar highland anorthosites (Hui et al 2013) have led to a reevaluation of what has appeared for decades to be one of the definitive results of the study of lunar samples: i.e., that the sources of lunar magmas-and, by inference, the entire Moon-are much poorer in water than the Earth; indeed the Moon had been described as "bone dry" (Newsom and Taylor 1989). In particular, direct measurements of water in incompletely degassed, primitive lunar glasses made in several laboratories have shown that water concentrations are similar to those observed in magmas from Earth's depleted upper mantle (Saal et al 2008;Chen et al 2015;Hauri et al 2015;Wetzel et al 2015) and that the isotopic composition of this water is approximately chondritic (Friedman et al 1974;Saal et al 2013;Barnes et al 2014;Füri et al 2014;Tartèse et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Water contents of apatite grains in mare basalts range from 0 to 6050 ppm H 2 O (Figure 2 and Table S5). These are the highest water contents measured in lunar samples [6][7][8][9] . Both high-Ti (10044 and 75055) and low-Ti (12039 and 14053) mare basalts contain apatite grains with abundant water.…”
mentioning
confidence: 99%
“…Volatile data from apatites in lunar basalts and alkali-suite clasts from McCubbin et al (2010) show a conflicting trend with lower OH -and higher Cl/F in rocks that have more alkali feldspar (i.e. more K-rich).…”
Section: Figurementioning
confidence: 99%
“…Apatite data are from McCubbin et al (2010). Water estimates from apatite assume 95 % crystallisation prior to apatite crystallisation.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation